Medical imaging systems technology - Leondes, Cornelius T. (Singapore : World Scientific Publishing, 2005)
v. 1. Analysis and computational methods --v. 2. Modalities --v. 3. Methods in general anatomy --v. 4. Methods in diagnosis optimization --v. 5. Methods in cardiovascular and brain systems.